Analisis Pupuk Kandang Ayam dan Biourine Terhadap Pertumbuhan dan Hasil Dari Benih dan Punggul Tanaman Kangkung Darat (Ipomea Reptans) - Ketut Agung Sudewa; Luh Komang Sulasmini Mudra (GEMA AGRO, 2018)
This study aims to determine the effect of chicken manure and biourine on the growth of stem of ground water kangkung, so it is known that the best type of fertilizer used for growth and yield of kangkung plants after the first harvest. This experiment used a randomized block design (RBD) with a factorial experimental pattern consisting of two factors. The first factor is the dosage of biourine (B) consisting of 4 levels ie B0: control, B1: 200 L ha-1, B2: 400 L ha-1, and B3: 600 L ha-1. The second factor is dose of cow manure (K) consist of 2 levels ie K0: control and K1: 20 ton ha-1. The results concluded that there was no interaction between the treatment of chicken manure with biourin liquid fertilizer to all growth variables and the results observed in ground kangkung plants derived from stump except the variables of the harvest index. Treatment of chicken manure 20 tons ha-1 gave the highest economical fresh weight per plant that is 70.48 g and increased by 84.02% compared to the economical fresh weight per plant obtained in the treatment without chicken manure is 38.30 g, while the treatment dose of 400 L ha-1 biourine fertilizer gave the highest economical fresh weight per plant that is 55.66 g and increased by 7.63% compared to the economical fresh weight per plant obtained in the treatment without biourine fertilizer ie 51.71 g.